Efektivitas pelatihan mindfulness untuk mengatasi insomnia pada mahasiswa - Awidha Dwi Wijayaningsih; Muhimmatul Hasanah; Ima Fitri Sholichah (University of Muhammadiyah Malang, 2022)
The goal of this study tested the effectiveness of Mindfulness training to overcome insomnia in college students.The number of participating subjects amounted to 8 people in the weight category, with four people in each group(experiment and control). Treatment was given to subjects in the experimental group as many as four meetings with11 sessions within one month. For control is given a mindfulness diary to find out the emotional condition and sleep of the subject. The study used the Jakarta Psychiatric Study Group – Insomnia Rating Scale as a pre-test and post-test to measure insomnia levels before and after treatment. The data analysis technique used in the study was the Mann-Whitney U Test. The results showed that the experimental group’s results (Mdn=7) were higher than those of the control group (Mdn=15.8). Mann-Whitney’s test results showed a significant difference in pain scores between the experimental and control groups (N experiment = 4, Control = 4, Z =-2,337; p=0.019). This can be seen in the decrease in insomnia score in the experimental group. Mindfulness training proved to be appropriate for overcoming insomnia in college students.